A comparison of tooth retention and replacement across 15 countries in the over-50s - Stock, Christian; Jürges, Hendrik; Shen, Jing; Bozorgmehr, Kayvan; Listl, Stefan (Community dentistry and oral epidemiology, 2016)
Objectives Oral diseases are still among the most common chronic diseases globally with substantial detrimental impact especially on elderly people's health and well-being. However, limited evidence exists on international variation in the oral health status of the older population. We aimed to examine international variation in tooth loss and tooth replacement in the general population aged between 50 and 90 years. Methods A cross-sectional analysis of data from the fifth wave of the Survey of Health, Ageing and Retirement in Europe (SHARE) was conducted. The data cover 14 European countries (Austria, Belgium, Czech Republic, Denmark, Estonia, France, Germany, Italy, Luxembourg, the Netherlands, Slovenia, Spain, Sweden, and Switzerland) and Israel, and they were collected during the year 2013. Age-specific percentages of the population having all natural teeth, the age-specific numbers of natural (and artificial) teeth, and the age-specific percentages of full, partial, or no replacement of missing teeth were assessed with stratification by country. It was further evaluated to which extent proposed oral health goals concerning tooth loss at higher ages had been achieved. Results In total, 62 763 individuals were included in the study. Age-standardized mean numbers of natural teeth exhibited substantial variation, ranging from 14.3 (Estonia) to 24.5 (Sweden). The oral health goal of retaining at least 20 teeth at age 80 years was achieved by 25% of the population or less in most countries. A target concerning edentulism (≤15% in population aged 65-74 years) was reached in Sweden, Switzerland, Denmark, France, and Germany. Tooth replacement practices varied especially for a number of up to five missing teeth which were more likely to be replaced in Austria, Germany, Luxembourg, and Switzerland than in Israel, Denmark, Estonia, Spain, and Sweden. Conclusions This study suggests that the age-specific number of natural teeth and the practice of tooth replacement in the over 50s differ substantially among the included countries. The present results may be helpful in the formulation and evaluation of oral health goals in the older population.
First published: 28 December 2015
Gesehen am 06.09.2019